2000
DOI: 10.1073/pnas.97.10.5551
|View full text |Cite
|
Sign up to set email alerts
|

A deletion in a photoreceptor-specific nuclear receptor mRNA causes retinal degeneration in the rd7 mouse

Abstract: The rd7 mouse, an animal model for hereditary retinal degeneration, has some characteristics similar to human flecked retinal disorders. Here we report the identification of a deletion in a photoreceptor-specific nuclear receptor (mPNR) mRNA that is responsible for hereditary retinal dysplasia and degeneration in the rd7 mouse. mPNR was isolated from a pool of photoreceptorspecific cDNAs originally created by subtractive hybridization of mRNAs from normal and photoreceptorless rd mouse retinas. Localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
170
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 26 publications
11
170
2
Order By: Relevance
“…At P16, shortly after eye opening at P14, white retinal spots were present over the entire retina [Haider et al, 2001]. The number of retinal spots decreased by 5 months of age and completely disappeared by 16 months [Akhmedov et al, 2000]. This was consistent with the disappearance of rosettes, suggesting an association of white spots with rosettes.…”
Section: Mouse Models Of Nr2e3 Diseasessupporting
confidence: 64%
See 2 more Smart Citations
“…At P16, shortly after eye opening at P14, white retinal spots were present over the entire retina [Haider et al, 2001]. The number of retinal spots decreased by 5 months of age and completely disappeared by 16 months [Akhmedov et al, 2000]. This was consistent with the disappearance of rosettes, suggesting an association of white spots with rosettes.…”
Section: Mouse Models Of Nr2e3 Diseasessupporting
confidence: 64%
“…Consistent with the recessive mode of inheritance of human ESCS, GFS and CRPD, heterozygote mice were normal, and a slow, but progressive degeneration of both the rod and cone systems was only observed in rd7/rd7 mice [Akhmedov et al, 2000;Haider et al, 2001]. Starting at P12, the presence of waves, whorls, and rosettes was observed in the outer nuclear layer of the retina [Haider et al, 2001].…”
Section: Mouse Models Of Nr2e3 Diseasesmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar to ESCS in humans, the rd7 retina has excess cones that express mostly S-cone opsin (Haider et al, 2001). Rod and cone function measured by electroretinography (ERG) is near normal in young adults but significantly declines in older mice as a result of degeneration of both rods and cones (Akhmedov et al, 2000;Ueno et al, 2005;Haider et al, 2006). These phenotypes of human ESCS and rd7 mice support a role for Nr2e3 in rod/cone development by demonstrating how its mutations lead to disease.…”
Section: Nr2e3 Is a Dual Transcription Regulator Required For Terminamentioning
confidence: 80%
“…Genetic analysis revealed that these mice carry a homozygous 380-bp deletion in the coding region of the Nr2e3 cDNA (Akhmedov et al, 2000;Haider et al, 2001), due to mRNA splicing defects resulting from an L1-retrotransposon insertion (Chen et al, 2006). This leads to a frame-shift with a premature termination.…”
Section: Nr2e3 Is a Dual Transcription Regulator Required For Terminamentioning
confidence: 99%